The Computed Tomography in vascular affections. - Wozniak, Angélica; Zubiaurre, Jorge (Cirugía del Uruguay, 1984)
This work includes discussion of the characteristics of vascular pathologies by computad tomography, emphasis being laid on aneurisms and dlssections of the aorta.